Assessing Student Social Studies Learning: Effects of Learning Environment, Inquiry, and Student Learning Interest - Rosfiani, Okta; Akbar, Ma’ruf; Neolaka, Amos (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractThis study aims to examine the effect of the learning environment, inquiry, and learning interest on student social studies learning assessment. The participants involved in this study are 130 students from public primary schools in South Jakarta. Data collection consists of social studies learning score, learning environment scale, inquiry scale, and learning interest scale. The results of the study show that the learning environment, inquiry, and learning interest directly influenced student social studies learning assessment in which inquiry and learning interest have a significant effect on student social studies learning assessment.AbstrakPenelitian ini bertujuan untuk menguji pengaruh lingkungan belajar, inkuiri, dan minat belajar terhadap penilaian belajar Ilmu Pendidikan Sosial (IPS) siswa. Peserta yang terlibat adalah 130 siswa dari sekolah dasar negeri di Jakarta Selatan. Pengumpulan data terdiri dari skor pembelajaran IPS, skala lingkungan belajar, skala inkuiri, dan skala minat belajar. Hasil penelitian menunjukkan bahwa lingkungan belajar, inkuiri, dan minat belajar secara langsung mempengaruhi penilaian belajar IPS siswa. Dimana inkuiri dan minat belajar memiliki pengaruh yang signifikan terhadap penilaian pembelajaran IPS.How to Cite : Rosfiani, O., Akbar, M., Neolaka, A. (2019).  Assessing Student Social Studies Learning: Effects of Learning Environment, Inquiry, and Student Learning Interest. TARBIYA: Journal of Education in Muslim Society, 6(1), 46-57. doi:10.15408/tjems.v6i1.11593.